Creative, Thus Connected: The Power of Sociometric Creativity on Friendship Formation in Gifted Adolescents—A Longitudinal Network Analysis of Gifted Students. Issue 168 (8th November 2019) - Hopp, Manuel D. S.; Zhang, Zhitian Skylor; Hinch, Leeanne; O'Reilly, Colm; Ziegler, Albert
Abstract: The current study's purpose is to explore the influence of peer‐perceived creativity (sociometric creativity) on the short‐term development of friendships during a summer program for high ability students. Specifically, the two main objectives of our study are: (1) How did students' friendships network and sociometric creativity network evolve in the summer program? (2) How did sociometric creativity influence the friendship formation? The longitudinal study was conducted at the beginning, middle and the end of a 3‐week long program for gifted students in Ireland. The sample consisted of Irish gifted students (N = 702, aged 13–18 years, 52% female, over thirty‐one classes). Overall, our longitudinal multilevel and multigroup social network analysis shows that gifted adolescents formed reciprocated friendship ties and cohesive peer group structures in the investigated period; similar age and the same gender predicted friendship formation. Regarding the sociometric creativity, they tended to nominate a similar age and same gender student as very creative. Moreover, the sociometric creativity positively influenced adolescents' friendship networks on a dyadic level, indicating that adolescents select friends based on their perception of the other student's creativity. Further results, explanations, and implications are discussed.